Risk of pancreatic adenocarcinoma in chronic pancreatitis. Issue 6 (1st December 2002) - Malka, D; Hammel, P; Maire, F; Rufat, P; Madeira, I; Pessione, F; Lévy, P; Ruszniewski, P
Abstract : Background: The risk of pancreatic cancer in patients with chronic pancreatitis (CP) is difficult to assess. Previous studies, mostly case control studies or studies relying on data case registers, reported relative risks varying from 2.3 to 18.5. Methods: We studied a prospective, single centre, medical-surgical cohort of 373 consecutive patients (322 (86%) men, median age 40 years) with proven CP (alcoholic origin 85%) and a follow up of at least two years (median follow up 9.2 years; range 2.0–34.8) in order to exclude pancreatitis revealing pancreatic cancer. We calculated the age and sex standardised incidence ratio (SIR) as the ratio of the number of observed cases of pancreatic cancer in this cohort to the number of expected cases, as provided by the French National Cancer Register. Results: Four cases of pancreatic adenocarcinoma (1.1% of patients) were observed in 3437 patient years (expected number of cases 0.15; SIR 26.7, 95% confidence interval (CI) 7.3–68.3; p=0.00002). In a second analysis in which patients lost to follow up were considered to be followed up until the end point without having developed pancreatic adenocarcinoma (4762 patient years), SIR was 19.0 (CI 5.2–48.8; p=0.00007). Conclusion: Patients with CP have a markedly increased risk of pancreatic cancer compared with the general population.